Case series: Cariprazine in early-onset schizophrenia - Ivanova, Elena; Maslinkova, Desislava; Polnareva, Nadia; Milanova, Vihra (Frontiers in Psychiatry, 2023)
Introduction: Negative symptoms are part of the clinical manifestations of schizophrenia and their presence is associated with a poorer prognosis, significantly limited vocational opportunities, impaired quality of life and social functioning. In the clinical practice, treatment of negative symptoms in patients with schizophrenia, is a challenge. We present two cases of young patients with predominantly negative symptoms during treatment with an atypical antipsychotic, administered in a stable dose and therapeutic range, and for at least 4 weeks prior to the Cariprazine switch. Methods: Two patients (men aged 21 and 22) with schizophrenia, exhibiting predominantly negative symptoms, are presented. Their diagnosis was based on, DSM-5 criteria (295.10). Patients were treated with Cariprazine at a daily dose of 4.5mg. They were followed for a period of 18 months and assessed with Positive and Negative Syndrome Scale (PANSS), Global Assessment of Functioning (GAF) and Clinical Global Impression-Severity (CGI-S), at the fourth week of initiation of treatment with Cariprazine, at 6 months, at 12 months and at 18 months. Their mean initial value was 75.5 on PANSS, 4.0 on CGI-S, and 52.5 on GAF. Both patients were treated with stable doses of atypical antipsychotic - Risperidone at a daily dose of 4,5mg. Cross-titration to Cariprazine was initiated, from 1.5mg daily dose up to 4,5mg daily dose, during a period of 2 weeks. Results: After 18 months of treatment with Cariprazine at a daily dose of 4. 5mg, the following results were reported: mean value was 57.5 on PANSS, 3.0 on CGI-S, and 74.5 on GAF. The overall PANSS mean score decreased by 23.8%, the CGI-S mean score improved by 25% and the mean GAF score increased by 29.5%. The positive PANSS subscale score decreased minimally, from 20 to 16, while for the negative subscale the improvement was 29.8%. Cariprazine was well tolerated by patients and no side effects were observed from it during therapy. Discussion: After 18 months Cariprazine succeeded in improving negative symptoms, global functioning, and global clinical impression. In young schizophrenic patients with a predominance of negative symptoms, the prescription of Cariprazine may be a successful alternative.